Enzymatic constituents in crossbred buck semen - KALE, M M; TOMER, O S (The Indian Journal of Animal Sciences, 2013)
A study was conducted an 10 crossbred buck's (Alpine x Beetal (7), Saanen x Beetal (1) semen for 5 enzymatic constituents (HYL, GOT, GPT, AKP, ACP) during 3 seasons. Season significantly (P